Skeletal Muscle in Healthy Subjects versus Those with GNE -Related Myopathy: Evaluation with Shear-Wave US—A Pilot Study - Carpenter, Elizabeth L.; Lau, Heather A.; Kolodny, Edwin H.; Adler, Ronald S. (Radiology, 2015)
To determine whether quantitative differences in shear-wave velocity (SWV) exist between normal skeletal muscle and those affected by GNE-related myopathy and to examine the effects of muscle anisotropy, depth, and axial preload on SWV in a healthy control group. This study was approved by the institutional review board and compliant with HIPAA. Informed consent was obtained from all study volunteers. Eight patients (four women and four men aged 30-50 years) with genetically and biopsy-proved GNE-related myopathy and five healthy volunteers (three women and two men aged 27-33 years) underwent SWV imaging with use of a 9-MHz linear transducer. The gastrocnemius muscles were evaluated in the patients with GNE-related myopathy, and the gastrocnemius, vastus lateralis, and rectus femoris muscles were evaluated in the healthy cohort. The effect of muscle anisotropy, axial preload, and sample volume depth were examined in the healthy cohort. The effect of anisotropy at a fixed depth and preload were examined in the patients with GNE-related myopathy. Irrespective of the muscle, the mean SWV was significantly higher with the transverse orientation than with the longitudinal orientation (P < .001). In the healthy cohort, the mean SWV for superficial measurements was significantly lower than that for deep measurements (P < .02). The mean SWV with preload was significantly higher with compression (P < .001) for the rectus femoris only. The mean SWV was significantly lower in patients with GNE-related myopathy than in control subjects (P < .02). SWV parametric imaging may provide a useful quantitative adjunct in the assessment of disease activity in patients with GNE-related myopathy. There is diminished SWV and muscle anisotropy in GNE-related myopathy.